2022
DOI: 10.1002/htj.22582
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of MHD nanofluid flow and heat transfer in a circular porous medium containing a Cassini oval under the influence of the Lorentz and buoyancy forces

Abstract: This paper reports our study on the flow characteristics and heat transfer performance of magnetohydrodynamics (MHD) nanofluid in an innovative porous, circle-shaped enclosure incorporating a Cassini oval cavity using the Darcy law. The MHD nanofluid considered in this study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(14 citation statements)
references
References 70 publications
(80 reference statements)
0
11
0
Order By: Relevance
“…In their other work for Ra = 10 4 -10 6 , Bose et al (2013) reported the effect of an adiabatic fin propped from the heated upright wall taking the bottom wall cold and the curved wall adiabatic. Jalili et al (2022c) have numerically investigated the magneto-hydrothermal behavior of Al 2 O 3 -H 2 O nanofluid in a circular porous cavity containing a Cassini oval cavity. They have studied the effect of Lorentz and buoyant forces on the thermal performance.…”
Section: Hybrid Nanofluid Convectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their other work for Ra = 10 4 -10 6 , Bose et al (2013) reported the effect of an adiabatic fin propped from the heated upright wall taking the bottom wall cold and the curved wall adiabatic. Jalili et al (2022c) have numerically investigated the magneto-hydrothermal behavior of Al 2 O 3 -H 2 O nanofluid in a circular porous cavity containing a Cassini oval cavity. They have studied the effect of Lorentz and buoyant forces on the thermal performance.…”
Section: Hybrid Nanofluid Convectionmentioning
confidence: 99%
“…In the background of relatively few pioneering works (Incropera, 1988; Biswas et al , 2015; Biswas et al , 2017; Das and Basak, 2017; Lukose and Basak, 2021; Hamzah et al , 2021), most of the studies address complex phenomena (Biswas et al , 2016a; Jalili et al , 2019; Sarkar et al , 2021; Mondal et al , 2022) involving multiple physics like buoyancy, nanofluid (Rahimi et al , 2019; Ghalambaz et al , 2020; Dutta et al , 2021; Dogonchi et al , 2018; Jalili et al , 2022a), hybrid nanofluid (Sarkar et al , 2015; Ghalambaz et al , 2019; Ali, 2020; Biswas et al , 2021a, 2021b; Manna and Biswas, 2021; Jalili et al , 2022b), magnetic field (Kabeel et al , 2015; Manna et al , 2021a; Giwa et al , 2021; Jalili et al , 2021; Jalili et al , 2022d), porous medium (Comini et al , 1974; Bejan et al , 2004; Biswas et al , 2017; Debayan and Basak, 2017; Manna et al , 2021b; Jalili et al , 2022c), microorganisms (Biswas et al , 2021c, 2021d, 2021e), etc. The studies are found to exist in simple (Lewis, 1987; Biswas et al , 2016a; Manna et al , 2019) to complex geometries (Mandal et al , 2022; Saha et al , 2022a, 2022b; Hussain and Oztop, 2021; Biswas et al , 2021d; Al-Farhany et al , 2021; Bhatti et al , 2021) without or with embedded obstructions (Biswas et al , 2021e; Das, and Basak, 2017; Hussain and Oztop, 2021; Mallick et al , 2021; Sivaraja and Sheremet, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…(2009) further extended their investigations on variable thickness sheets. Many researchers ( Jalili et al. , 2022a; Jalili et al.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous scientists and researchers have good practice in nanofluids usage in various fields [1,2,3,4,5]. In this regard, Manjunatha et al [6] presented the convective heat in ternary nanofluids flowing through a stretching surface.…”
Section: Introductionmentioning
confidence: 99%